2004
DOI: 10.1001/archpedi.158.8.753
|View full text |Cite
|
Sign up to set email alerts
|

New Users of Antipsychotic Medications Among Children Enrolled in TennCare

Abstract: The proportion of TennCare children who became new users of antipsychotics nearly doubled from 1996 to 2001, with a substantial increase in use of antipsychotics for attention-deficit/hyperactivity disorder, conduct disorder, and affective disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
130
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 154 publications
(135 citation statements)
references
References 31 publications
5
130
0
Order By: Relevance
“…This was driven by a large increase in the prescription of secondgeneration antipsychotics, whereas the prescription of first-generation antipsychotics began to fall during the latter five years of this time period. The increase in antipsychotic prescribing among children and adolescents is even more dramatic in the United States (US) where two to six-fold increases have been observed during similar time periods, with similar trends to those in the UK noted in the use of first-and second-generation preparations (Cooper et al, 2004;Aparasu et al, 2005;Cooper et al, 2006;Olfson et al, 2006).…”
Section: Introductionmentioning
confidence: 77%
“…This was driven by a large increase in the prescription of secondgeneration antipsychotics, whereas the prescription of first-generation antipsychotics began to fall during the latter five years of this time period. The increase in antipsychotic prescribing among children and adolescents is even more dramatic in the United States (US) where two to six-fold increases have been observed during similar time periods, with similar trends to those in the UK noted in the use of first-and second-generation preparations (Cooper et al, 2004;Aparasu et al, 2005;Cooper et al, 2006;Olfson et al, 2006).…”
Section: Introductionmentioning
confidence: 77%
“…[19][20][21] However, children are being prescribed antipsychotics to control behavioral symptoms of ADHD or comorbid aggression and for other nonapproved indications. 6,22,23 In addition, psychiatric polypharmacy involving antipsychotics and stimulants has increased in recent years. Cooper et al (2004) found over a 3-fold increase in the proportion of children who were prescribed antipsychotics for ADHD or conduct disorders from 1996-2001 in the TennCare program.…”
Section: ■■ Methods Study Design and Data Sourcementioning
confidence: 99%
“…6,22,23 In addition, psychiatric polypharmacy involving antipsychotics and stimulants has increased in recent years. Cooper et al (2004) found over a 3-fold increase in the proportion of children who were prescribed antipsychotics for ADHD or conduct disorders from 1996-2001 in the TennCare program. 22 Fullerton et al (2012) found that the percentage of ADHD youths taking antipsychotics increased from 8% in 1996 to 18% in 2005, which was primarily driven by the increased use of atypical antipsychotics (AAPs).…”
Section: ■■ Methods Study Design and Data Sourcementioning
confidence: 99%
See 1 more Smart Citation
“…22 Although the evidence strongly suggests that atypicals are effective, it is by no means definitive, yet the use of atypicals as combination therapy with antidepressants in unipolar patients is apparently common, at least as I have understood recent utilization data. 23 It may be because this particular combination is a new approach or because clinicians are seeing a robust response, but concerns about side effects and long-term adverse outcome may complicate matters. Of course, the costs of these agents can also be prohibitive.…”
Section: Dr Trivedimentioning
confidence: 99%